Book Review Essays and Reviews. Issue 1 (1st July 2019) - Message, Kylie; Foster, Eleanor; Cobley, Joanna; Chang, Shih; Reeve, John; Gassin, Grace; Gush, Nadia; McNaughton, Esther; Jacknis, Ira; Campbell, Siobhan
Abstract : Book Review Essays Museum Activism. Robert R. Janes and Richard Sandell, eds. New York: Routledge, 2019. New Conversations about Safeguarding the Future: A Review of Four Books. - A Future in Ruins: UNESCO, World Heritage, and the Dream of Peace. Lynn Meskell. New York: Oxford University Press, 2018. - Keeping Their Marbles: How the Treasures of the Past Ended Up in Museums—And Why They Should Stay There. Tiffany Jenkins. Oxford: Oxford University Press, 2016. - World Heritage and Sustainable Development: New Directions in World Heritage Management. Peter Bille Larsen and William Logan, eds. New York: Routledge, 2018. - Safeguarding Intangible Heritage: Practices and Politics. Natsuko Akagawa and Laurajane Smith, eds. New York: Routledge, 2019. Book Reviews The Filipino Primitive: Accumulation and Resistance in the American Museum. Sarita Echavez See. New York: New York University Press, 2017. The Art of Being a World Culture Museum: Futures and Lifeways of Ethnographic Museums in Contemporary Europe. Barbara Plankensteiner, ed. Berlin: Kerber Verlag, 2018. China in Australasia: Cultural Diplomacy and Chinese Arts since the Cold War. James Beattie, Richard Bullen, and Maria Galikowski. London: Routledge, 2019. Women and Museums, 1850–1914: Modernity and the Gendering of Knowledge. Kate Hill. Manchester: Manchester University Press, 2016. Rethinking Research in the Art Museum. Emily Pringle. New York: Routledge, 2019. A Natural History of Beer. Rob DeSalle and Ian Tattersall. New Haven, CT: Yale University Press, 2019. Fabricating Power with Balinese Textiles: An Anthropological Evaluation of Balinese Textiles in the Mead-Bateson Collection. Urmila Mohan. Chicago: University of Chicago Press, 2018.